Economic evaluations and usefulness of standardized nursing terminologies. - Stone PW; Lee N; Giannini M; Bakken S (International Journal of Nursing Terminologies & Classifications)
PURPOSE: To review different types of economic analyses commonly found in healthcare literature, discuss methodologic considerations in framing economic analyses, identify useful resources for economic evaluations, and describe the current and potential roles of standardized nursing terminologies in providing cost and outcome data for economic analysis. DATA SOURCES: The Advanced Billing Concepts Code Resource-based Relative Value Scale and Nursing Outcomes Classification. DATA SYNTHESIS: Using case studies, the applicability of standardized nursing terminologies in cost-effectiveness analysis is demonstrated. While there is potential to inform specific questions, comparisons across analyses are limited because of the many outcome measures. CONCLUSIONS: Including a standardized quality-of-life measure in nursing terminologies would allow for the calculation of accepted outcome measures and dollars per quality adjusted life years gained. IMPLICATIONS FOR PRACTICE: The nurse's ability to assess and contribute to all aspects of rigorous economic evidence is an essential competency for responsible practice.